Multi-resolution monitoring of the 2023 maui wildfires, implications and needs for satellite-based wildfire disaster monitoring - David P. Roy; Hugo De Lemos; Haiyan Huang; Louis Giglio; Rasmus Houborg; Tomoaki Miura (Science of Remote Sensing)
The August 2023 wildfires over the island of Maui, Hawaii were one of the deadliest U.S. wildfire incidents on record with 100 deaths and an estimated U.S. $5.5 billion cost. This study documents the incidence, extent, and characteristics of the 2023 Maui wildfires using multi-resolution global satellite fire products, and in so doing demonstrates their utility and limitations for detailed fire monitoring, and highlights outstanding satellite fire observation needs for wildfire monitoring. The NASA 500 m Moderate Resolution Imaging Spectroradiometer (MODIS) burned area product is compared with PlanetScope 3 m burned areas that were mapped using a published deep learning algorithm. In addition, all the August 2023 active fire detections provided by MODIS on the Terra and Aqua satellites and by the Visible Infrared Imaging Radiometer Suite (VIIRS) on the S-NPP and NOAA-20 satellites are used to investigate the geographic and temporal occurrence of the fires and their incidence relative to the 3 m mapped burned areas. The geographic and diurnal variation on the fire radiative power (FRP), available with the active fire detections, is presented to examine how energetically the fires were burning. The analysis is undertaken for all of Maui and for the town of Lahaina that was the major population center that burned. Satellite active fires were first detected August 8th, 2023 in the early morning (1:45 onwards) on the western slopes of Mt. Haleakalā and were last detected August 10th in the early morning (at 2:46) over Lahaina and on the western slopes of Mt. Haleakalā. The FRP available with the VIIRS satellite active fire detections indicate that the fires burned less intensely from the beginning to the end of this three day period, the nighttime fires generally burned more intensely than the daytime fires, and the most intensely burning fires occurred over Lahaina likely due to the high fuel load in the buildings compared to the vegetation that burned elsewhere. The MODIS 500 m burned area product was too coarse to map most of the 18 burned areas that were mapped unambiguously at 3 m resolution with PlanetScope and covered 29.60 km2, equivalent to about 1.6% of Maui. This study highlights the limitations of systematically derived satellite fire products for assessment before, during and after wildfire disaster events such as those experienced over Maui. The needs for future fire monitoring of wildfire disaster events, and the recommendation for a fire monitoring satellite constellation, are discussed.